Meritve temperaturnega polja v masivnem betonu z optičnimi kabli - Humar, Nina (Gradbeni vestnik, 2022)
Large concrete dams are among the most frequently monitored structures, which is understandable when considering the consequences of dam or equipment failure. In recent decades, due to the rapid development of materials and equipment, we have witnessed great progress in measuring techniques and methods for monitoring dam conditions. Our research focused on monitoring the temperature field in the early stages of concrete hardening in massive structures, which is a good indicator for the predicting the material properties of hardened concrete. The classical approach to temperature field monitoring is based on the use of temperature sensors with point data capture. Due to the limitations of using such sensors in large structural blocks, which we encounter in dam construction, it is difficult to create a more complex picture of the temperature field. For this purpose, the use of fiber optic cables, which allow linear capture of temperature measurements, has proven to be a very effective method. The article presents the basics of using fiber optic cables for temperature monitoring in massive concrete structures and shows their practical applicability for temperature monitoring during the hydration process in the construction of a structural block on the spillway section of the Brežice dam.
Keywords: betonske pregrade; hidratacija; masivni beton; optična vlakna; temperatura